The Impact of Institutional and Managerial Ownership, Dividend Policy, and Company Size on the Financial Performance and Their Consequences for Firm Valuation - Tresnawati, Rina (Universitas Mercu Buana, 2024)
Objectives: The objective of this study is guided by agency theory, which seeks to reduce conflicts of interest between business owners and agents. Institutional ownership, management ownership, and dividend payout ratio are regarded as the primary determinants of a company's financial success, as measured by Return on Equity (ROE). Finally, financial performance can affect firm value, as measured by Price to Book Value (PBV).Methodology: The research population consists of manufacturing sector enterprises that registered with the BEI between 2017 and 2021. The analysis approach utilized is Moderated Regression Analysis (MRA), which is a multivariate linear regression model with interaction (multiplication of more than one independent variable). Finding: H1 and H2 are rejected as the computed t is less than the t table and the sig value exceeds α 0.05. H3 and H4 are valid since the projected t value surpasses the t table and the sign value is less than 0.05. H5 is also regarded as an MRA, despite its negative consequences.Conclusion: Institutional ownership and managerial ownership do not affect financial performance or return on equity. Meanwhile, the dividend payout ratio has a favorable and large impact on financial performance. This shows that if the choice of dividend policy is of good quality and in line with the company's interests, it will have a beneficial influence on financial success. ROE has a positive and significant effect on company value/price book value (PBV). Meanwhile, company size (M) has a significant moderating value but the effect is negative. This means that variable M has a negative moderating influence on the effect of ROE on PBV.